2001
DOI: 10.1029/2000gl012255
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of reactive biogenic VOCs at a high altitude site in late autumn

Abstract: Abstract. Volatile organic compounds (VOCs) at the Sonnblick Observatory, Austria (3106 m a.s.1.) were measured in autumn 1999 using proton-transfer-reaction mass spectrometry (PTR-MS). Anthropogenic V OCs at this remote site, such as benzene and toluene (50 pptv to 2 ppbv), were primarily traced to air from urban areas. In mid-November, following a hard freeze in the central Alps, a different pattern of VOCs developed similar to that seen with C5 and C6 leaf wound compounds (0.5 to 5 ppbv range). The common o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…High concentrations of GLVs have been found in the forest atmosphere in autumn when senescing and litter leaves thaw after freezing spells of weather and emit GLVs (Karl et al, 2001). Fall et al (1999) demonstrated with aspen, beech, and clover that after leaf detachment, emissions of GLVs were not dependent on light, and emissions were enhanced greatly as detached leaves dried out.…”
Section: Voc Emissions After Leaf Fallmentioning
confidence: 98%
“…High concentrations of GLVs have been found in the forest atmosphere in autumn when senescing and litter leaves thaw after freezing spells of weather and emit GLVs (Karl et al, 2001). Fall et al (1999) demonstrated with aspen, beech, and clover that after leaf detachment, emissions of GLVs were not dependent on light, and emissions were enhanced greatly as detached leaves dried out.…”
Section: Voc Emissions After Leaf Fallmentioning
confidence: 98%
“…Several other species also have been reported to be detected at mass 69, such as methyl butanal, ethyl vinyl alcohol, and furan (Christian et al, 2004;Karl et al, 2001). However, isoprene was often found as the dominant species at mass 69 within various kinds of air masses .…”
Section: Mass 69mentioning
confidence: 99%
“…(Kirstine and Galbally, 2004;Olofsson et al, 2003). Local weather conditions can also result in the release of GLVs; high concentrations of GLVs (up to 5 ppbv) were seen in the Alps after a freezing spell, and were attributed to emission from damaged cells upon thawing (Karl et al, 2001). The recent study of Joutsensaari et al (2005) indicated that these types of stress induced emissions from plants can form increased levels of SOA over healthy plants and are likely to be important aerosol precursors.…”
Section: Introductionmentioning
confidence: 99%